Constitutional Reform in the Russian Federation: for and Against - S. A. Tsyplyaev (Теоретическая и прикладная юриспруденция)
The article discusses the prospects for constitutional reform in the Russian Federation and the arguments of supporters and opponents of the reform. Considering the basic models of republican government in the modern world, the author comes to the conclusion that the presidential-parliamentary republic, which is the basis of the Constitution of the Russian Federation, is optimal for our country. According to the author, the French model of a semi-presidential republic is closest to the Russian one. The author also formulates proposals for improving the constitutional legislation of Russia.